5-Year Activity and Participation Outcomes of the First Successful Pediatric Bilateral Hand Transplantation: A Case Report. (2nd November 2022) - Levy, Todd J.; Tyner, Callie E.; Amaral, Sandra; Lefkowitz, Debra S.; Kessler, Sudha K.; Levin, L. Scott
Abstract: Aims: Describe the 5-year outcomes of the first successful pediatric bilateral hand transplantation. Methods: The child underwent quadrimembral amputation at age two and received bilateral hand allografts at age eight. Rehabilitation included biomechanical, neurorehabilitation, and occupational approaches in acute and outpatient settings. Therapist observed outcomes, patient-reported measures, and parent-reported measures were repeated over a 5-year period. Results: Observation assessments revealed functional dexterity skills and modified independence to full independence with self-care activities. The parent reported the child had moderate difficulty with upper extremity functioning 25-, 41-, and 48-months post-transplantation, and mild difficulty at 60-months; the child reported no difficulties in this domain at 41 months. Five years post-transplantation the child reported enjoying many age-appropriate activities, and high-quality peer relations were endorsed by both parent and child. Conclusion: The child developed hand movements for daily activities and was completing daily activities with improved efficiency. Health-related quality of life outcomes were favorable.